Communication architecture for biodiversity information retrieval (CABIR) - Dhillon, Sarinder Kaur; Lim, L.H.S.; Dimyati, Kaharudin; Merican, Amir Feisal (Faculty of Science, University of Malaya, 2009)
This paper focused on biodiversity database integration. Firstly, the problems are studied and explained. They are divided into four broad categories, which are technical, political, syntactical and semantical. Following this, the approaches to build a database integration system were reviewed after which, the mediator based approach was selected. A new database integration system, which is called CABIR (Communication Architecture for Biodiversity Information Retrieval) was built and discussed thoroughly in this paper. A performance test was also conducted to measure the efficiency of the CABIR system. The development of CABIR system is expected to contribute in the field of biodiversity as this system could link distributed biodiversity databases regardless of the heterogeneity and the platform they were built upon.